Finance and growth : new evidence on the role of insurance - Wan Ngah, Wan Azman Saini; Smith, Peter (Wiley-Blackwell Publishing Asia, 2011)
This paper provides new evidence that sheds light on the impact of insurance sector development on output growth, capital accumulation and productivity improvement, using data from 51 countries (developed and developing) during 1981-2005. The dynamic panel data analysis results demonstrate that insurance sector development affects growth predominantly through productivity improvement in developed countries, while in developing countries it promotes capital accumulation.